Social support and unsupportive interactions in relation to depressive symptoms: Implication of gender and the BDNF polymorphism. (2nd January 2020) - Woods, Robbie; McInnis, Opal; Bedard, Marc; Asokumar, Ajani; Santoni, Samantha; Anisman, Hymie; Matheson, Kimberly; McQuaid, Robyn J.
ABSTRACT: Reduced levels of brain derived neurotrophic factor (BDNF), through its role in neurogenesis and neuroplasticity, may be involved in the evolution and maintenance of depression. Depression has also been tied to fewer social relationships, which can vary by gender. Thus, we assessed whether the functional single nucleotide polymorphism (SNP) on the BDNF gene, Val66Met, moderated the relationship between depressive symptoms and perceived social support and unsupportive relationships, and whether these associations differed by gender. Among 945 students, (n = 667 females; n= 278 males), depressive scores were inversely related to social support, and positively related with unsupportive relations. Females reported greater social support and depressive scores compared to males. A3-way interaction was found between unsupportive relations, the Val66Met SNP, and gender, such that irrespective of genotype, females displayed astrong relationship between unsupport and depressive scores. Male Met carriers displayed this relationship, but this was less apparent among males with the Val/Val genotype. The Val66Met SNP did not moderate the link between support and depressive scores. This BDNF SNP may serve to moderate the links between psychosocial factors and depressive symptoms, but such links are nuanced, being gender-dependent and varying with the nature of the social interactions experienced.